2016
DOI: 10.1016/j.euroneuro.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Potential contribution of the Alzheimer׳s disease risk locus BIN1 to episodic memory performance in cognitively normal Type 2 diabetes elderly

Abstract: In recent years, several promising susceptibility loci for late-onset Alzheimer’s disease (AD) were discovered, by implementing genome-wide association studies (GWAS) approach. Recent GWAS meta-analysis has demonstrated the association of 19 loci (in addition to the APOE locus) with AD in the European ancestry population at genome-wide significance level. Since Type 2 Diabetes (T2D) is a substantial risk factor for cognitive decline and dementia, the 19 single nucleotide polymorphisms (SNPs) that represent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The hippocampus is a bilateral brain structure located in the temporal lobe on which learning and memory are critically dependant [ 53 ]. Episodic memory impairment is a hallmark of neurodegenerative diseases, such as Alzheimer’s disease, which are neurobiologically linked to the hippocampus [ 54 ]. Liu and colleagues [ 48 ] reported that Pb exposure induced significant microgliosis and astrogliosis in hippocampus of young mice.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is a bilateral brain structure located in the temporal lobe on which learning and memory are critically dependant [ 53 ]. Episodic memory impairment is a hallmark of neurodegenerative diseases, such as Alzheimer’s disease, which are neurobiologically linked to the hippocampus [ 54 ]. Liu and colleagues [ 48 ] reported that Pb exposure induced significant microgliosis and astrogliosis in hippocampus of young mice.…”
Section: Discussionmentioning
confidence: 99%
“…rs6733839 carriage is associated with higher pTau181 levels in CSF (Crotti et al, 2019). Homozygote individuals for rs6733839*T show worse episodic memory (Greenbaum et al, 2016). This SNP is in LD with Class.…”
Section: Discussionmentioning
confidence: 91%
“…rs6733839 carriage is associated with higher pTau181 levels in CSF ( Crotti et al, 2019 ). Homozygote individuals for rs6733839*T show worse episodic memory ( Greenbaum et al, 2016 ). This SNP is in LD with rs4663105, which occurs in the NONHSAT187478.1 lncRNA gene, possibly associated with neurodegenerative diseases (ncRPheno).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a meta-analysis of 74,046 participants found that BIN1 rs6733839 SNP was related to AD [ 33 ]. Greenbaum et al observed an association between well-established AD susceptibility SNP rs6733839 and episodic memory, and it can an important genetic risk factor for MCI among elderly individuals [ 34 ]. Based on the above studies, we have reason to believe that rs6733839 and rs7561528 gene polymorphism occupy a vital position in the pathogenesis of MCI by affecting the expression of BIN1.…”
Section: Discussionmentioning
confidence: 99%